Enactment of corporate laws for building legal environment and their effectiveness - Hamzah, . (Opción, 2019)
This study investigates the current legal environment ofIndonesia in the light of new enactment of laws and effectiveness oftheir enforcement. The SPSS software was used to carry out regressionanalysis. The findings show a positive relationship between legalenvironment and legal effectiveness, however the enactment of newlaws was found to be unrelated and insignificant due to significantuncertainties and past legacy still present in the Indonesian law. Inconclusion, it is time for creating public awareness to understand whatcorporate activities could be harmful to them.